A handbook of human resource management practice - Armstrong, Michael (London : Sterling, VA : Kogan Page, 2001)
This eighth edition of this work has been fully updated to take account of the latest developments in HRM. Detailing every aspect of the human resource function, the comprehensive handbook considers the function in relation to the needs of the business as a whole. Recognizing HRM as a strategic process, Michael Armstrong offers clear, practical advice on how companies can maximize the effectiveness of the HRM function and ensure that it makes a major contribution to organizational success.
Includes bibliographical references and index.
oif 16/02/15.
Loan
Keywords: Personnel management; Human resource management